CROHN'S DISEASE COMPLICATED BY ILEOSIGMOID FISTULA: ASSESSMENT AND MANAGEMENT UPDATE. (22nd January 2022) - Benammi, Sarah; Calini, Giacomo; Abdalla, Solafah; Mathis, Kellie
Abstract: BACKGROUND: The preoperative evaluation of Crohn's-related ileosigmoid fistula (ISF) is complex with multiple preoperative diagnostic modalities available. Intraoperative management is also complicated when deciding whether to repair the fistula or resect the involved sigmoid. How these choices impact outcomes is not clear. We aim to evaluate the impact of sigmoid resection versus conservative fistula repair on postoperative complications when treating ISF. METHODS: Patients with Crohn's disease (CD) undergoing ileocolic resection in the setting of an ISF between January 1, 2007 and December 31, 2017 were identified. A retrospective chart review was conducted to collect data on preoperative workup, intra-operative technique, and 30-day complications. Intra-abdominal sepsis was defined as the presence of an intra-abdominal abscess or anastomotic leak from the sigmoid colon postoperatively. Univariate comparisons were performed between those undergoing primary repair versus sigmoid resection with primary anastomosis. RESULTS: 61 patients (62.3% female) with a median age of 37 years (range, 18-73)were included. Computed tomography enterography (CTE) and magnetic resonance enterography (MRE) each had a sensitivity of 100% versus 42% sensitivity for colonoscopy. When accounting for pre-operative endoscopy results, patients with endoscopic sigmoidal mucosal CD more often underwent sigmoid resection than patients with a normal sigmoidal mucosa or only a solitary fistulous opening in the sigmoid colon (p<0.001). When comparing primary repair vs sigmoid resection there was no difference in the occurrence of intra-abdominal septic complications (p=0.342) or anastomotic leak complication (p=0.239). CONCLUSION: In summary, our study shows that conservative repair of the fistula is a safe option. Appropriate patient assessment and preoperative identification of the fistula is critical so that the management strategies for ISF and the potential implications can be discussed with the patient. CTE and MRE are the modalities of choice to diagnose ISF, while colonoscopy has a role in staging the burden of mucosal disease in the sigmoid colon. These tests help guide surgical decision-making with respect to resection versus primary repair of the sigmoid colon and will allow patients in whom the sigmoid colon is an innocent bystander to undergo a less extensive operation.